The influence of parents socio-economic conditions on student achievement in junior high schools - Dewi Rahmawati Safitri; Happy Fitria; Rohana Rohana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The research aims to identify, describe, and analyze whether or not the influence of the socio-economic conditions of parents on student achievement in Junior High Schools in Kedaton Peninjauan Raya District. This type of research is quantitative research. Population in this research as many as 464 students. A research sample of around 216 students was established by using the sampling technique proportional random sampling using the formula of slovin 5% of significance. The technique of Data collection by using questionnaires and documentation. Then data analysis using linear regression analysis with SPSS program. The result showed that the socio-economic conditions of parents affect student achievement. This paper is expected to provide directions and solutions for educational institutions to carry out education properly and appropriately by following the environmental conditions of the community in improving the quality of education.